2018
DOI: 10.3171/2017.5.jns162799
|View full text |Cite
|
Sign up to set email alerts
|

Serum glucose/potassium ratio as a clinical risk factor for aneurysmal subarachnoid hemorrhage

Abstract: In this study, the serum glucose/potassium ratio of patients with aneurysmal SAH at admission was significantly correlated with H-K grade and GOS score at discharge. Therefore, this ratio was useful for predicting prognosis of aneurysmal SAH, especially in severe cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 33 publications
(27 reference statements)
1
40
1
1
Order By: Relevance
“…Recently, Fujiki et al reported that serum GPR, glucose and potassium level at admission were significantly correlated with poor outcome at 3 months ( 7 ). Our results do not entirely coincide with their results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Fujiki et al reported that serum GPR, glucose and potassium level at admission were significantly correlated with poor outcome at 3 months ( 7 ). Our results do not entirely coincide with their results.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some clinical studies have reported that hyperglycemia is related with the risk of poor outcome and delayed cerebral ischemia (DCI) after aSAH ( 5 , 6 ). Recent reports have suggested that the glucose to potassium ratio (GPR) is significantly correlated with cerebral vasospasm and functional outcome ( 7 , 8 ). The purpose of the present study was to calculate the plasma GPR in patients with aSAH and to determine whether this ratio is associated with the risk of 3-month mortality.…”
Section: Introductionmentioning
confidence: 99%
“…24 Fujiki et al reported that a high serum GLU/K ratio in patients with aneurysmal SAH would be useful in predicting poor prognosis. 25 Park et al suggested that catecholamine crises in globus pallidus and deep white matter were key pathophysiologic factors in CO intoxication. 26 In another study, norepinephrine and dopamine were found to be high in pericardial and cerebrospinal fluids in patients who died of CO intoxication.…”
Section: Discussionmentioning
confidence: 99%
“…8 Additionally, these changes have been found in some diseases involving acute brain injury, such as severe traumatic brain injury and aneurysmal subarachnoid hemorrhage. [9][10][11] The serum glucose/potassium ratio (GPR) is calculated as the serum glucose level divided by the serum potassium level. Its elevation has been reported to be highly associated with increasing severity and poor prognosis of certain pathological conditions, e.g., carbon monoxide poisoning.…”
Section: Introductionmentioning
confidence: 99%